LIBERALISME HUKUM ISLAM DI INDONESIA (DAMPAK TERHADAP PERKEMBANGAN HUKUM ISLAM DI INDONESIA) - Qori Rizqiah H Kalingga (JURNAL JUSTIQA, 2020)
Islamic law reflects a set of divine rules or norms that govern the relationship between humans and other humans in social life, with objects and their natural environment. Divine norms that govern the relationship system are rules in a special sense or rules of pure worship that regulate the way or direct relationship between humans and their God, and muamlah regulates humans and others and other creatures in their environment. At the next level, divine norms are constructed in the form of binding rules for Muslims called Islamic Law. Islamic law has universal characteristics and applies to all Muslims in a place or country at one time. Respect human dignity as a unit of body and soul and honor human beings as a whole, and its implementation is driven by faith and morals. Thus the existence of Islamic law will create a conducive, peaceful and orderly situation (Rahmatan Lil'alamiin) which touches both the outer and inner aspects. Liberalism or liberal is an ideology, a philosophical viewpoint and a political tradition based on the understanding that freedom is the main political value. Freedom is a separate goal for liberalists, without human freedom cannot live and society cannot function, therefore the idea of freedom in every time and place always plays a role. The term liberal Islam was not well known and paid attention to by people in Indonesia, especially since the number of supporters was only a minority, but recently it has become very popular.